DESTiny, an online farm-wide tool to estimate the net carbon emissions of a pasture-based dairy farms in South Africa - Riana Reinecke; Riana Reinecke; James N. Blignaut; James N. Blignaut; James N. Blignaut; Heinz H. Meissner; Pieter A. Swanepoel (Frontiers in Sustainable Food Systems)
The dairy farming industry is an important contributor to both South Africa’s economy and food security. However, dairy in South Africa, like elsewhere in the world, has come under scrutiny because of animal welfare concerns and contributions to greenhouse gas (GHG) emissions. To address GHG mitigation, we have constructed a farm-level system dynamics model to assess both the emissions, and capture and storage of carbon (C) on farms, to determine whether farms are net emitters of C (i.e., sources) or sequestrators (i.e., sinks). We have considered nutrient flows, the type and volume of feed, the effluent management system, various parameters relating to the herd dynamics, and the overall effect on the farm economy. The resulting online Dairy Environment Sustainability Tool (DESTiny) can help dairy farmers adopt sustainable practices, as well as improve competitiveness and financial sustainability while reducing the farm’s emissions profile, thereby building value-chain and consumer trust. DESTiny can be considered a science-informed evidence-based tool for estimating, monitoring and understanding nutrient and C flows in dairy production systems. It is also a web-based tool (see https://assetresearch.org.za/destiny-tool/) with a user-interface which allows remote users, researchers, practitioners, farmers and technicians ease of access while integrating the system dynamics models with on-farm realities.